2017
DOI: 10.21276/obgyn.2017.4.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome after diagnosis of oligohydramnios at term

Abstract: Objectives: The aim of the study was to evaluate the effects of oligohydramnios on maternal and fetal outcome at term pregnancy. Methodology: A case control study on pregnancy outcome in 100 women with AFI<5cm after 37 completed weeks of pregnancy compared with 100 controls with no oligohydramnios with matched age and parity. Results: Non stress test (NST) was non-reactive in 38% of oligohydramnios and 20% of controls and was statistically significant (P<0.05). Ominous fetal heart patterns were seen in 60% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
1
0
1
Order By: Relevance
“…In our study, 66 (29.5%) newborns had a poor Apgar score, with a (15,17). The study conducted by Chate P et al (18) revealed that pregnant women with an AFI less than 50 mm at term had higher rates of intrapartum complications and lower Apgar scores compared to those with higher AFI values. However, this outcome contrasted with the findings of Pasquini L et al (19), where no significant differences were observed in delivery modes or neonatal outcomes in pregnancies with oligohydramnios compared to those with normal AFI.…”
Section: Discussionsupporting
confidence: 50%
“…In our study, 66 (29.5%) newborns had a poor Apgar score, with a (15,17). The study conducted by Chate P et al (18) revealed that pregnant women with an AFI less than 50 mm at term had higher rates of intrapartum complications and lower Apgar scores compared to those with higher AFI values. However, this outcome contrasted with the findings of Pasquini L et al (19), where no significant differences were observed in delivery modes or neonatal outcomes in pregnancies with oligohydramnios compared to those with normal AFI.…”
Section: Discussionsupporting
confidence: 50%
“…Kumar et al, Thobbi VA et al, and Chidanandaiah et al reported NICU admissions in the range of 38-40% due to fetal distress, birth asphyxia, and meconium aspiration. 21,25,26 Kahkhaie et al documented 1% of NICU admissions in the neonates born to mothers with AFI <5 cm. 27 In our study, the neonates born to mothers with AFI <5 cm had good APGAR scores at 5 minutes and no neonate scored below 7 due to good intrapartum monitoring and immediate resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…En otro estudio llevado a cabo en India, (15) se compararon 50 pacientes con oligohidramnios con 50 normales, encontrando que 46% del grupo de estudio tuvieron APGAR al minuto <=7 frente a 18% del grupo control, no siendo significativa esta diferencia (p>0,05), como tampoco lo fue en un estudio adelantado por Nankali y cols., (16) a pesar que todos los del grupo con ILA <=5 tuvieron APGAR <=7 frente a 41% del grupo control.…”
unclassified